1996
DOI: 10.1063/1.471116
|View full text |Cite
|
Sign up to set email alerts
|

New model for electron-impact ionization cross sections of molecules

Abstract: A theoretical model for electron-impact ionization cross sections, which has been developed primarily for atoms and atomic ions, is applied to neutral molecules. The new model combines the binary-encounter theory and the Bethe theory for electron-impact ionization, and uses minimal theoretical data for the ground state of the target molecule, which are readily available from public-domain molecular structure codes such as GAMESS. The theory is called the binaryencounter Bethe (BEB) model, and does not, in prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
362
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 523 publications
(410 citation statements)
references
References 38 publications
27
362
1
2
Order By: Relevance
“…We also modified the BEB cross section in this case to use a reduced value of U for the outermost valence molecular orbital, 2 g , as we did in Ref. 1. When a molecular orbital is dominated by an atomic orbital-in this case by the 3p orbital of S-with high principal quantum numbers, its kinetic energy is high, and makes the cross section too low because U enters the cross section formula, Eq.…”
Section: B Carbon Disulfide (Cs 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…We also modified the BEB cross section in this case to use a reduced value of U for the outermost valence molecular orbital, 2 g , as we did in Ref. 1. When a molecular orbital is dominated by an atomic orbital-in this case by the 3p orbital of S-with high principal quantum numbers, its kinetic energy is high, and makes the cross section too low because U enters the cross section formula, Eq.…”
Section: B Carbon Disulfide (Cs 2 )mentioning
confidence: 99%
“…In earlier publications, 1,2 we have demonstrated that a new theoretical method, the binary-encounter-Bethe ͑BEB͒ model, provides reliable electron-impact total ionization cross sections for molecules using very simple input data for the ground state, all of which can be obtained from standard molecular wave function codes. There are no adjustable or fitted parameters in the theory.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while computations can provide a starting point for developing an excitation/dissociation cross section, in the form of the energy dependence and approximate magnitude of the cross section, validation against swarm measurements, and adjustment where necessary, remain essential steps. Likewise, some processes, such as electron-impact ionization of polyatomic molecules, remain out of reach of present first-principles computational techniques; despite the many successes of simple approximations such as the BEB model [36] and the modified additivity rule [37], measurements of these cross sections are the preferable alternative, especially as they can provide cross sections for individual fragment ions. As logic would suggest, critical data needs can be addressed most efficiently through a pragmatic approach that draws upon the best features of computation, experiment, and simulation.…”
Section: Discussionmentioning
confidence: 99%
“…(1) to avoid making the cross section unrealistically small for valence orbitals with many nodes. 9 " 10 Note that t+(u+l)n approaches t as the incident energy T increases. The Born approximation is valid at high t, and it has only t in the denominator.…”
Section: Theoretical Basis For the Beb Modelmentioning
confidence: 99%